From Trendelenburg to PERTs: Evolution in the Management of Massive Pulmonary Embolism - Pavan Thangudu (Methodist DeBakey Cardiovascular Journal)
Massive pulmonary embolism (MPE) is a serious condition affecting the pulmonary arteries and is difficult to diagnose, triage, and treat. The American College of Chest Physicians (AHA) and the European Society of Cardiology (ESC) have different classification approaches for PE, with the AHA defining three subtypes and the ESC four. Misdiagnosis is common, leading to delayed or inadequate treatment. The incidence of PE-related death rates has been increasing over the years, and mortality rates vary depending on the subtype of PE, with MPE having the highest mortality rate. The current definition of MPE originated from early surgical embolectomy cases and discussions among experts. However, this definition fails to capture patients at the point of maximal benefit because it is based on late findings of MPE. Pulmonary Embolism Response Teams (PERTs) have emerged as a fundamental shift in the management of MPE, with a focus on high-risk and MPE cases and a goal of rapidly connecting patients with appropriate therapies based on up-to-date evidence. This review highlights the challenges in diagnosing and managing MPE and emphasizes the importance of PERTs and risk stratification scores in improving outcomes for patients with PE.